A study on the attitude towards patronizing the select store among the residents of SS18, Subang Jaya / Zaharoff Azman - Azman, Zaharoff (1998)
As time and convenience has become important in this modern times, the concept of convenience stores has been accepted by the fast moving community which values the positive usage of time. The growth of convenience store industry among oil companies have been accompanied by new challenges where they have to compete closely with each other and also due to the increasing of demand as the customers are becoming more sophisticated and knowledgeable. In this modern days, beside focussing on time and convenience, it is also important to maintain a positive customer attitude in determining success in the retail industry. Therefore, certain aspects of marketing in which previously may be insignificant to the management such as customer attitudes have to be taken into consideration for today's market environment. The study of the interrelationships between attitudes and behavior is very important to any business organisations. Organisations that can attain positive customer attitude for their company and products are enable to keep pace with the competitiveness of the market environment by drawing in more customers and maintain customer loyalty. In addition, positive customer attitude leads to the greater capitalising of opportunities that the market offers, strenghtening the organisation, and even capitalising on the competitors' weaknesses.